Influence of need for affiliation on small business customer loyalty - Aaron Joyal; Carol Bartlo (Small Business International Review)
The need for affiliation (nAff) facet of David McClelland’s (1961) triad of needs is prevalent in psychology and business literature. Typically, nAff is referenced in combination with McClelland’s additional two triads: need for achievement (nAch) and need for power (nPow). Isolating the nAff construct, this study investigates the linkage of affiliation inclination of small business customers to their perceived value of retail servicescapes, filling a gap in the literature on nAff by evaluating the extent to which customer perceptions of servicescapes correspond to loyalty behaviors. Using online questionnaires, we analyzed data from 265 small business customers. This study suggests that servicescapes evoke customers’ feelings and reactions and customers subsequently form opinions of the servicescapes and the associative business. The study results indicate that customers’ need to be attached to small businesses and be satisfied with their small business experiences drive loyalty. When customers have positive servicescape reactions and become loyal customers, small businesses benefit. The findings of this study offer valuable insights for small business owners around the world, suggesting that investing in servicescape initiatives could contribute to their ongoing business success.